2015
DOI: 10.1371/journal.pone.0134136
|View full text |Cite
|
Sign up to set email alerts
|

Associations and Synergistic Effects for Psychological Distress and Chronic Back Pain on the Utilization of Different Levels of Ambulatory Health Care. A Cross-Sectional Study from Austria

Abstract: The aim of this analysis was to assess the impact of chronic back pain and psychological distress on the utilization of primary and secondary levels of care in the ambulatory health care sector in Austria - a country without a gatekeeping system. Additionally, we aimed to determine if the joint effect of chronic back pain and psychological distress was higher than the impact of the sum of the two single conditions. The database used for this analysis was the Austrian Health Interview Survey, with data from 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…Therefore, the sheer presence of a usual GP, which is politically and informally promoted as the first point of contact and coordinator of care, is insufficient to regulate pathways of patients within the health care system. This is particularly evident for patients with chronic conditions, who otherwise would benefit most from appropriate pathways of care (7,15,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sheer presence of a usual GP, which is politically and informally promoted as the first point of contact and coordinator of care, is insufficient to regulate pathways of patients within the health care system. This is particularly evident for patients with chronic conditions, who otherwise would benefit most from appropriate pathways of care (7,15,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our study, an association of multiple pain, pain severity, and depressive disorders was found in the elderly population in a recent study in Germany [ 55 ]. Moreover, studies suggest that the interaction between pain and mental disorders act synergistically with regard to higher health care utilisation [ 33 ], or exit from the labour market [ 16 , 32 ]. However, whether depression and anxiety are a cause or consequence of pain, or whether they are the results of different paths of the same pathogenesis, still remains unresolved and under discussion [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focussing on social factors related to pain either do not differentiate between pain in different body sites [ 1 , 3 , 6 , 14 , 16 , 20 , 21 , 25 27 , 31 ], or focus narrowly on pain in one specific area like back pain [ 11 , 15 , 30 , 32 , 33 ], low back pain [ 7 , 10 ], headache [ 9 , 19 , 22 ], on pain due to a specific underlying pathogenesis [ 4 , 8 ], a specific disease like migraine [ 28 , 29 ], or osteoarthritis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…That means that the effect of pain and ADL deficits on healthcare utilisation was much higher than merely the addition of the effects of the single conditions [27]. Similarly, a synergistic effect on healthcare utilisation (primary care and specialised outpatient care) was found in the general adult population in Austrians regarding chronic back pain and anxiety/depression [28]. Loss of productivity is one of the main factors causing costs due to back pain.…”
Section: Economic Aspects Of Back Painmentioning
confidence: 98%